Home Practice: Irish women, Diaspora and Somatic Principles of Hosting - Meehan, Emma (Repertório, 2019)
Dr. Emma Meehan is a Research Fellow at Coventry University’s Centre for Dance Research. She received her BA and PhD from the Drama Department, Trinity College, Dublin, where she taught part-time on the BA and MA programmes. She also worked as the administrator for the Arts Technology Research Lab at Trinity College to support the Digital Arts and Humanities Doctoral Programme. Her doctoral research focused on the work of Irish choreographer Joan Davis, who combines dance and somatic practices in creating interactive, site-specific performances. Emma is associate editor for Journal of Dance and Somatic Practices, and was co-convenor of the Performance as Research Working Group at the International Federation for Theatre Research from 2013-2017.